`I`m not the police`: practical strategies for sport coach mentors to develop trust and trustworthiness - Ives, B.; Clayton, B.; Gale. L.; Taylor, W.; Leeder, T. M.; Nichol, A. J. (Qualitative Research in Sport, Exercise and Health, 2023)
This paper examines trust and trustworthiness in sport coach mentor-mentee relationships. Specifically, we investigate the place and importance of trust from the mentor`s perspective and establish how trustworthy impressions are actively developed. Guided by theoretical ideas addressing trust relations, we conducted 18 online, two-to-one semi-structured interviews with nine mentors affiliated with two National Governing Bodies (NGBs) of sport. Data were subjected to a phronetic, iterative analysis, which involved inductive and deductive sensemaking and an interactive writing process. Key findings suggested a) that the mentors defined trust as a crucial construct in the development of mentee motivation, learning, and engagement, b) establishing trustworthy impressions was important for the mentors` material and non-material interests, c) mentors reported how mentees were initially aloof due to an apparent distrust of NGBs, and d) mentors used numerous interactional strategies to create trustworthy impressions. These included i) deformalising mentor-mentee relationships, ii) actively demonstrating reliability as mentors, iii) using mutually beneficial lies to simultaneously secure buy-in and build mentee confidence and self-esteem, iv) illustrating their own fallibility as sport coaches, v) considering the value of displaying their own coaching competency, and vi) developing mentees` competencies through empowerment. The findings offer practical strategies for NGBs and other [non]sporting bodies to support mentors in creating trustworthy impressions and building successful mentoring relationships.